STUDY ON PIRANDAI POWDER FOR MARGIN LIST WOMEN WITH OSTEOPOROSIS IN TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
In modern era non-communicable diseases are rapidly increasing in developing countries including India. (Aquigley Maria, et al., 2006). Osteoporosis, a silent epidemic has become a major health hazard in recent years, afflicting over 2000 million of people worldwide.(Svedbom, et al., 2013) Osteoporosis is one of the most widespread metabolic bone disorders, affecting one in three women and one in twelve men at some point in their lives. (Meryl, et al., 1997)Pirandai powder with high calcium and fibre content which helps to increase the serum calcium level and to reduce body weight. This was decided to distribute to the selected respondents. Pirandai powder also gave quicker healing of broken bones. The nutritional status of the osteoporotic women was assessed by investigating the anthropometric measurements of the respondence and the dietary pattern using food- frequency method. The shelf life of the pirandai powder was tested once in three day up to 30 days. Microbial and nutrient analysis were carried out for the studies.